PELATIHAN KETERAMPILAN OLAHRAGA, KETERAMPILAN MEMBUAT STRAP MASKER, DAN PENYULUHAN KEBERSIHAN LINGKUNGAN SEKOLAH - Siti Napfiah; Nok Izatul Yazidah; Dian Fitri Argarini; Dean Abner (JPM PAMBUDI, 2021)
This PMBP activity aims to increase the interest and knowledge of students or the public in doing sports with good and correct techniques, Increase awareness of students or the public to store masks in a clean and safe place when not worn or not advised to wear a mask on the chin, and Increase students' awareness of the importance of maintaining the cleanliness of the school environment at SD Kristen Brawijaya 1 Malang. The method used in the implementation of PMBP is in the form of counseling methods, training, and question and answer tones. The activity began with observation at SD Kristen Brawijaya 1 Malang. Followed by core activities in the form of Sports Skills Training, Mask Strap Making Skills Training, and School Environment Hygiene Counseling. The target in this PMBP activity is the students of SD Kristen Brawijaya 1 Malang. The result of the implementation of PMBP at SD Kristen Brawijaya I Malang is: Students are able to practice basic techniques in sports that have been taught,, students are able to answer questions related to sports techniques performed, when asked questions after activities,, Many students already have the awareness to put masks in a clean and safe place. As well as not wearing masks in dagu, students have begun to have an awareness of the cleanliness of the school environment, judging by the enthusiasm of students in carrying out mutual assistance. From the discussion above can be said to be successful, because from the observations after the training activities there is a better change. But there is still a slight drawback, there are still some students who have to be reminded not to wear masks on the chin. Perhaps in the upcoming activities will be given more understanding for how to wear a mask properly and properly.